2024
DOI: 10.2196/50506
|View full text |Cite
|
Sign up to set email alerts
|

Association of Digital Engagement With Relaxation Tools and Stress Level Reduction: Retrospective Cohort Study

Inbar Breuer-Asher,
Marilyn D Ritholz,
David L Horwitz
et al.

Abstract: Background Stress is an emotional response caused by external triggers and is a high-prevalence global problem affecting mental and physical health. Several different digital therapeutic solutions are effective for stress management. However, there is limited understanding of the association between relaxation components and stress levels when using a digital app. Objective This study investigated the contribution of relaxation tools to stress levels ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Web or mobile applications for cognitive interventions, such as Lumosity, are also becoming more widespread. A retrospective cohort study about using a behavioral health app for digital intervention revealed a significant decrease in stress symptoms during a period of 1-6 weeks of app use that was maintained during a period of 6-10 weeks [33].…”
Section: Mobile Technology Application and Virtual Reality Nature Int...mentioning
confidence: 99%
“…Web or mobile applications for cognitive interventions, such as Lumosity, are also becoming more widespread. A retrospective cohort study about using a behavioral health app for digital intervention revealed a significant decrease in stress symptoms during a period of 1-6 weeks of app use that was maintained during a period of 6-10 weeks [33].…”
Section: Mobile Technology Application and Virtual Reality Nature Int...mentioning
confidence: 99%